Differential role of APP and APLPs for neuromuscular synaptic morphology and function - Klevanski, Maja; Saar, Martina; Weyer, Sascha W.; Müller, Ulrike C. (Molecular and cellular neuroscience, 2014)
The analysis of mouse models indicated that APP and the related APLPs are important for synapse formation and function. The synaptic role of APP is, however, complex due to partially overlapping functions within the gene family. APP/APLPs are proteolytically cleaved and have both adhesive and signaling properties. Mice lacking individual APP family members are viable, whereas APP/APLP2 and APLP1/APLP2 double knockout (DKO) mice die shortly after birth. Here, we analyzed the morphology of the neuromuscular junction (NMJ) of lethal APLP1/APLP2-DKO mice in comparison to lethal APP/APLP2-DKO mutants and viable single KO mice. We report that, surprisingly, the NMJ phenotype of APLP1/APLP2-DKO mice shows striking differences as compared to APP/APLP2-DKO mice. Unexpectedly, APLP1/APLP2-DKO mice exhibit normal endplate patterning and lack presynaptic nerve terminal sprouting. However, at the level of individual synapses we show that APLP1/APLP2-DKO mice exhibit reduced size of pre- and postsynaptic compartments and reduced colocalization. As APP/APLP2-DKO and APLP1/APLP2-DKO mice show similar penetrance of early postnatal lethality, this suggests that deficits at the level of individual synapses due to impaired synaptic apposition and/or deficits in transmitter release may cause lethality. Using an in vitro cell-adhesion assay, we observed that APP trans-dimerization is considerably less efficient than APLP2 trans-interaction. Thus, differences between APP/APLP2 and APP/APLP1 NMJ formation may be in part explained by differences in APP/APLP2 trans-dimerization properties. Collectively, our study further highlights the distinct and essential role of APLP2 at NMJ synapses that cannot be compensated by APP.
Gesehen am 11.08.2020